If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18z + -17z + 3 = 17 Reorder the terms: 3 + 18z + -17z = 17 Combine like terms: 18z + -17z = 1z 3 + 1z = 17 Solving 3 + 1z = 17 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 1z = 17 + -3 Combine like terms: 3 + -3 = 0 0 + 1z = 17 + -3 1z = 17 + -3 Combine like terms: 17 + -3 = 14 1z = 14 Divide each side by '1'. z = 14 Simplifying z = 14
| 10-2r=6 | | -6.8(2p+5)-1.6(4p+6)= | | T=24m-4m^2 | | 16=4(n+1) | | h(-4)=-5 | | ix^2-8x+30=0 | | (7x^4+xy^2)dx+(x^2y+6y^5)dy=0 | | x=172+-3x | | 8(x+6)-24=4(2x+5) | | x=172+3x | | x=172 | | -6t^2+24t+14=t | | 2x-5y=36 | | 2x-17=-17+x+2 | | -(6-(a+1))=9-(5-(2a-3)) | | 10=2(h+2) | | -9x-8=6x+1 | | b-8+2b=15 | | x-8x^3+2=0 | | 4x^2=13x^2-9 | | (19b-7)-9(2b+3)=-6 | | 5=4q-7 | | -8t^2+48t-30=0 | | 1=2b-1 | | 5x+206x+30=3 | | 19-7-9(2b+3)=-6 | | 6(1)-y=9 | | -100=0.25x | | 0=t^2+6t-9 | | 4c+5=4c+3 | | 10=lx-3l | | x^2-6x-11=-8 |